Variation of 4 MV X-ray dose rate in fractionated irradiation strongly impacts biological endothelial cell response in vitro. (2nd January 2022) - Ben Kacem, Mariam; Benadjaoud, Mohamed A.; Dos Santos, Morgane; Buard, Valérie; Tarlet, Georges; Le Guen, Bernard; François, A.; Guipaud, O; Milliat, F; Paget, Vincent
Abstract: Purpose: Even though X-ray beams are widely used in medical diagnosis or radiotherapy, the comparisons of their dose rates are scarce. We have recently demonstrated in vitro (clonogenic assay, cell viability, cell cycle, senescence) and in vivo (weight follow-up of animals and bordering epithelium staining of lesion), that for a single dose of irradiation, the relative biological effectiveness (RBE) deviates from 1 (up to twofold greater severe damage at the highest dose rate depending on the assay) when increasing the dose rate of high energy X-ray beams. Material and methods: To further investigate the impact of the dose rate on RBE, in this study, we performed in vitro fractionated irradiations by using the same two dose rates (0.63 and 2.5 Gy.min −1 ) of high-energy X-rays (both at 4 MV) on normal endothelial cells (HUVECs). We investigated the viability/mortality, characterized radiation-induced senescence by using flow cytometry and measured gene analysis deregulations on custom arrays. Results: The overall results enlighten that, in fractionated irradiations when varying the dose rate of high-energy X-rays, the RBE of photons deviates from 1 (up to 2.86 for viability/mortality experiments performed 21 days postirradiation). Conclusion: These results strengthen the interest of multiparametric analysis approaches in providing an accurate evaluation of the outcomes of irradiated cells in support of clonogenic assays, especially when such assays are not feasible.